Meningococcal virulence in zebrafish embryos depends on capsule polysaccharide structure - Schipper, Kim; Preusting, Lisanne C.; van Sorge, Nina M.; Pannekoek, Yvonne; van der Ende, Arie (Frontiers in Cellular and Infection Microbiology, 2022)
Neisseria meningitidis or the meningococcus, can cause devasting diseases such as sepsis and meningitis. Its polysaccharide capsule, on which serogrouping is based, is the most important virulence factor. Non-encapsulated meningococci only rarely cause disease, due to their sensitivity to the host complement system. How the capsular polysaccharide structure of N. meningitidis relates to virulence is largely unknown. Meningococcal virulence can be modeled in zebrafish embryos as their innate immune system of the zebrafish embryo resembles that of mammals and is fully functional two days post-fertilization. In contrast, the adaptive immune system does not develop before 4 weeks post-fertilization. We generated isogenic meningococcal serogroup variants to study how the chemical structure of the polysaccharide capsule affects N. meningitidis virulence in the zebrafish embryo model. H44/76 serogroup B killed zebrafish embryos in a dose-dependent manner, whereas the non-encapsulated variant was completely avirulent. Neutrophil depletion was observed after infection with encapsulated H44/76, but not with its non-encapsulated variant HB-1. The survival of embryos infected with isogenic capsule variants of H44/76 was capsule specific. The amount of neutrophil depletion differed accordingly. Both embryo killing capacity and neutrophil depletion after infection correlated with the number of carbons used per repeat unit of the capsule polysaccharide during its biosynthesis (indicative of metabolic cost). Conclusion Meningococcal virulence in the zebrafish embryo largely depends on the presence of the polysaccharide capsule but the extent of the contribution is determined by its structure. The observed differences between the meningococcal isogenic capsule variants in zebrafish embryo virulence may depend on differences in metabolic cost.